Do outcomes after behavioral couples therapy differ based on the gender of the alcohol use disorder patient?. (March 2016) - O'Farrell, Timothy J.; Schreiner, Amy; Schumm, Jeremiah; Murphy, Marie
Abstract: Objective: This naturalistic study (conducted from 1992 to 1998) of behavioral couples therapy (BCT) compared female and male alcohol use disorder (AUD) patients on improvement and on drinking and relationship outcomes after BCT. We also evaluated gender differences on presenting clinical problems and extent of BCT participation. Method: Participants were 103 female and 303 male AUD patients (98.5% alcohol dependence, 1.5% alcohol abuse) and their heterosexual partners, mostly White in their forties. Couples received 20–22 BCT sessions over 5–6 months. Drinking outcomes were percentage days abstinent (PDA) and alcohol-related problems. Relationship outcome was Dyadic Adjustment Scale. Outcome data were examined at baseline, post-treatment, and 6- and 12-month follow-up. Presenting problems were demographics, alcohol problem severity, illicit drug use, emotional distress, and relationship adjustment. BCT participation was BCT attendance and BCT-targeted behaviors. Results: We found few differences between female and male patients, who did not differ on improvement and outcomes after BCT. Both females and males showed significant large effect size improvements through 12-month follow-up on PDA and alcohol-related problems, and significant small to medium effect size improvements on relationship adjustment. Both females and males had high levels of BCT participation. Gender differences in presenting clinical problems (females being lower on age, years problem drinking, and baseline PDA, and higher on emotional distress) did not translate into gender differences in response to BCT. Conclusion: Results showed no support for the suggestion that BCT might lead to greater improvement and better outcomes for female than male AUD patients on drinking or on relationship outcomes. Highlights: We compared behavioral couples therapy (BCT) for female and male alcoholics. Few differences were found between female and male alcoholic patients. They did not differ on drinking or relationship outcomes after BCT.